Lattice design and beam dynamics studies for the PLS-II - S. Shin (2018)
Pohang Light Source (PLS) [1] had operated for 14 year successfully. To meet the request of the increasing user community, the PLS-II that is the upgrade project of PLS have been carried out. Main design goals of the PLS-II lattice are to increase beam energy to 3 GeV, to increase number of insertion devices by factor of two (20 IDs), to increase beam current to 400 mA and to reduce beam emittance below 10 nm with existing PLS tunnel and injection system. Following the desired design criteria, DBA lattice had been chosen such that the full storage ring includes 12 long straight sections and 12 short straight sections for installation of insertion devices with keeping beam emittance as small as possible. Through the six months of commissioning in the later half of 2011 and user operation in full period of 2012, we have successfully operated 14 insertion devices operation and top-up operation with 200 mA beam current and 5.8 nm beam emittance. It is especially important that good understanding of the machine operation and limitations can be achieved by comparison of experimental and simulation data during realizing final PLS-II goal and stable operation. Therefore, this paper describes the results of lattice design and beam dynamics studies for the PLS-II [2,3] .© 2013 IOP Publishing Ltd and Sissa Medialab srl.